Wastewater engineering : treatment and reuse. - Metcalf and Eddy, Inc.; Tchobanoglous, George, 1935-; Burton, Franklin L. (Franklin Louis), 1927-; Stensel, H. David, ....- (Boston : McGraw-Hill, 2003)
Inhoudsopgave : 1 Wastewater Engineering: An Overview p.1 2 Constituents in Wastewater p.27 3 Analysis and Selection of Wastewater Flowrates and Constituent Loadingsp.153 4 Introduction to Process Analysis and Selection p.215 5 Physical Unit Operations p.311 6 Chemical Unit Processes p.475 7 Fundamentals of Biological Treatment p.545 8 Suspended Growth Biological Treatment Processes p.659 9 Attached Growth and Combined Biological Treatment Processes p.887 10 Anaerobic Suspended and Attached Growth Biological Treatment Processesp.983 11 Advanced Wastewater Treatment p.1035 12 Disinfection Processes p.1217 13 Water Reuse p.1345 14 Treatment, Reuse, and Disposal of Solids and Biosolids p.1447 15 Issues Related to Treatment-Plant Performance p.1633 App. A Conversion Factors p.1729 App. B Physical Properties of Selected Gases and the Composition of Airp.1737 App. C Physical Properties of Water p.1741 App. D Solubility of Dissolved Oxygen in Water as a Function of Salinityand Barometric Pressure p.1745 App. E MPN Tables and Their Use p.1749 App. F Carbonate Equilibrium p.1753 App. G Moody Diagrams for the Analysis of Flow in Pipes p.1757
Keywords: Afvalwaterzuivering